Autophagy in orthodontic tooth movement: advances, challenges, and future perspectives - Biao Li; Leilei Wang; Hong He (Molecular Medicine)
Abstract Orthodontics aims to correct misaligned teeth by repositioning them into their proper three-dimensional positions through periodontal remodeling triggered by orthodontic forces. Orthodontic tooth movement (OTM) is an aseptic inflammation process characterized by osteoclast-mediated bone resorption on the compression side and osteoblast-induced bone deposition on the tension side. Orthodontic forces primarily include compressive force (CF), tensile force (TF), and flow shear stress (FSS), meanwhile, hypoxia is concomitantly induced during force application. Autophagy is a highly conserved catabolic mechanism mediating cellular degradation and recycling and is classified into three main types: macroautophagy, microautophagy, and chaperone-mediated autophagy (CMA), distinguished by their substrate delivery mechanisms to lysosomes. This review will first outline common autophagy classifications, describe the basic process of macroautophagy, and discuss autophagy regulators, as well as the theories of OTM mechanisms. Furthermore, it will systematically elucidate roles and mechanisms of autophagy in OTM across different cell types, with specific emphasis on hypoxia, CF, TF, and FSS. Additionally, mitophagy and CMA will be addressed. Hopefully, this comprehensive analysis aims to provide a theoretical foundation for accelerating OTM and mitigating orthodontically induced inflammatory root resorption through autophagy modulation.